Perianal tuberculosis in an immunocompetent patient: A diagnostic enigma unraveled by caseating granulomas - Ranga, Ajmeera; Yadav, G Vamshi; Ahmed, Syed Arbaaz; Kumar, G Tarun (Indian Journal of Case Reports, 2026)
Perianal tuberculosis (TB) is an exceptionally rare form of extrapulmonary TB (